Self-mixing interference effects in tunable diode laser absorption spectroscopy - Masiyano, Dackson; Hodgkinson, Jane; Schilt, S.; Tatam, Ralph P. (Springer Science Business Media, 2009)
We report the effects of self-mixing interference on gas detection using tunable diode laser spectroscopy. For very weak feedback, the laser diode output intensity gains a sinusoidal modulation analogous to that caused by low finesse etalons in the optical path. Our experiments show that self-mixing interference can arise from both specular reflections (e.g. cell windows) and diffuse reflections (e.g. Spectralon™ and retroreflective tape), potentially in a wider range of circumstances than etalon-induced interference. The form and magnitude of the modulation is shown to agree with theory. We have quantified the effect of these spurious signals on methane detection using wavelength modulation spectroscopy and discuss the implications for real gas detector